Economic Opportunity and Evolution: Beyond Landscapes and Bounded Rationality. (21st May 2014) - Felin, Teppo; Kauffman, Stuart; Koppl, Roger; Longo, Giuseppe
<x xml:space="preserve">Abstract</x> The nature of economic opportunity has recently received significant attention in entrepreneurship, organization science and strategy. The notion of boundedly rational search on an (NK) opportunity landscape has been particularly relevant to these conversations and debates. We argue that the focus on bounded rationality and search is highly problematic for the fields of entrepreneurship and strategy and does not allow us to explain the origins of economic novelty. We contrast the NP problem with the frame problem to illustrate our point, and highlight the role of adjacent possibilities and novel affordances. We discuss the entrepreneurial and economic implications of these arguments by building on unique insights from biology, the natural and computational sciences. Copyright © 2014 Strategic Management Society.